Burden Sharing: Income, Inequality and Willingness to Fight. Issue 1 (2nd July 2018) - Anderson, Christopher J.; Getmansky, Anna; Hirsch-Hoefler, Sivan
Abstract : What explains citizens' willingness to fight for their country in times of war? Using six waves of the World Values Survey, this study finds that individual willingness to fight is negatively related with country-level income inequality. When income inequality is high, the rich are less willing to fight than the poor. When inequality is low, the poor and rich differ little in their willingness to fight. This change in the willingness to fight between low and high inequality countries is greater among the rich than among the poor. This article explores several explanations for these findings. The data are consistent with the argument that high inequality makes it more attractive for the rich to buy themselves out of military service.